(untitled) (Eurasian Research Bulletin, 2023)
An increase in the production of cytokines in the body of pregnant women in the reproductive period and the main mechanisms of their action were studied. The article highlights their studies of cytokine production in women of the Bukhara population. The conducted studies study the conditions for the production of cytokines (IL-1b, IL-6, IL-8) and inflammatory cytokines (IL-4, IL-10) in the body of women living in a hot climate, and apply them in practice.